KORELASI UNDANG-UNDANG NOMOR 35 TAHUN 2014 TERHADAP HUKUM ISLAM TENTANG PERLINDUNGAN ANAK DI MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Nazhif, Naufal; Taufiqurrohman; Rahim, Abdur (Cahaya Ilmu Bangsa, 2024)
Providing protection to children is the most important step because children are among those who need protection. Child Protection Law Number 35 of 2014 stipulates that children have the right to be protected from crimes, such as discrimination, physical and mental violence. In the context of Islamic law, the protection of children is also discussed in the Compilation of Islamic Law (KHI). KHI covers a variety of children's rights, including the right to maintenance, the right to education, the right to protection, and the right to inheritance. The purpose of this study is to determine the correlation of Law Number 35 Year 2014 to Islamic law on child protection in Madrasah Ibtidaiyah Ma'had Al-Zaytun. This research method uses a quantitative approach. Data collection in this study used observation and questionnaires to teachers of Madrasah Ibtidaiyah Ma'had Al-Zaytun. Data analysis used in this research is validity test, reliability test, and Pearson correlation test. The results showed that there is a positive and significant relationship between Law Number 35 Year 2014 and Islamic law in this study. This can be seen from the product moment correlation value of 0.470, which indicates a positive and significant relationship with a moderate level of relationship strength, because the coefficient value is in the coefficient interval range of 0.400 - 0.599. This finding shows that the higher the value of one variable, the greater the likelihood that the value of the other variable will increase, reflecting a significant relationship between the two variables studied. Keywords: Correlation, Law Number 35 of 2014, Islamic Law, Child Protection, Maqashid Sharia, Madrasah Ibtidaiyah.